2023
DOI: 10.1016/j.gocm.2023.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Advances in diagnosis, clinical management and molecular characterization of ovarian Brenner tumors

Abstract: Brenner tumors is a very uncommon ovarian epithelial neoplasm, morphologically resembling the transitional cell neoplasm of urinary tract. It is further classified into three subtypes as a disease spectrum based on histological examination and tumorigenesis: benign Brenner tumors, borderline Brenner tumors (BBTs), and malignant Brenner tumors (MBTs). The etiology of these tumors is not well understood, and literature is limited due to the rarity of this entity, but recent advances, particularly in molecular al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The decrease or absence of p16 protein expression observed in both borderline and malignant Brenner tumors with retained p16 expression in benign subtypes suggests that the loss of p16 may contribute to the progression from benign to borderline and malignant subtypes [ 6 ]. Furthermore, studies have demonstrated that the activation of the EGFR pathway and downstream co-activation of the Ras-MAPK pathway may also drive the progression [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease or absence of p16 protein expression observed in both borderline and malignant Brenner tumors with retained p16 expression in benign subtypes suggests that the loss of p16 may contribute to the progression from benign to borderline and malignant subtypes [ 6 ]. Furthermore, studies have demonstrated that the activation of the EGFR pathway and downstream co-activation of the Ras-MAPK pathway may also drive the progression [ 13 ].…”
Section: Discussionmentioning
confidence: 99%